Surface‐Dependent Activation of Model α‐Al2O3‐Supported P‐Doped Hydrotreating Catalysts Prepared by Spin Coating. Issue 64 (14th October 2020) - Garcia de Castro, Ricardo; Bertrand, Jérémy; Rigaud, Baptiste; Devers, Elodie; Digne, Mathieu; Lamic‐Humblot, Anne‐Félicie; Pirngruber, Gerhard; Carrier, Xavier
Abstract: Requirements for improved catalytic formulations is continuously driving research in hydrotreating (HDT) catalysis for biomass upgrading and heteroatom removal for cleaner fuels. The present work proposes a surface‐science approach for the understanding of the genesis of the active (sulfide) phase in model P‐doped MoS2 hydrotreating catalysts supported on α‐Al2 O3 single crystals. This approach allows one to obtain a surface‐dependent insight by varying the crystal orientations of the support. Model phosphorus‐doped catalysts are prepared via spin‐coating of Mo–P precursor solutions onto four α‐Al2 O3 crystal orientations, C(0001), A(11 2 ‾ 0), M(10 1 ‾ 0) and R(1 1 ‾ 02) that exhibit different speciations of surface ‐OH. 31 P and 95 Mo liquid‐state NMR are used to give a comprehensive description of the Mo and P speciation of the phospho‐molybdic precursor solution. The speciation of the deposition solution is then correlated with the genesis of the active MoS2 phase. XPS quantification of the surface P/Mo ratio reveal a surface‐dependent phosphate aggregation driven by the amount of free phosphates in solution. Phosphates aggregation decreases in the following order C(0001)≫M(10 1 ‾ 0)>A(11 2 ‾ 0), R(1 1 ‾ 02). This evolution can be rationalized by an increasing strength of phosphate/surface interactions on the different α‐Al2 O3 surface orientations from the C(0001) to the R(1 1 ‾ 02) plane. Retardation of the sulfidation with temperature is observed for model catalysts with the highest phosphate dispersion on the surface (A(11 2 ‾ 0), R(1 1 ‾ 02)), suggesting that phosphorus strongly intervene in the genesis of the active phase through a close intimacy between phosphates and molybdates. The surface P/Mo ratio appears as a key descriptor to quantify this retarding effect. It is proposed that retardation of sulfidation is driven by two effects: i) a chemical inhibition through formation of hardly reducible mixed molybdo‐phosphate structures and ii) a physical inhibition with phosphate clusters inhibiting the growth of MoS2 . The surface‐dependent phosphorus doping on model α‐Al2 O3 supports can be used as a guide for the rational design of more efficient HDT catalysts on industrial γ‐Al2 O3 carrier. Abstract : A surface science approach study of hydrotreating catalysts revealed a surface‐dependent phosphorus doping with implications on the genesis of the active phase. Dispersion and sulfidation extent were impacted upon phosphorus doping. However, phosphorus impacted each model catalyst differently.